DIGITALISATION OF CRISIS MANAGEMENT AND RESOURCE BALANCING FOR EDUCATIONAL QUALITY ASSURANCE AT A DISPLACED UNIVERSITY - Oleksandr Spivakovsky; Daria Malchykova; Viktoria Yatsenko (Інформаційні технології і засоби навчання)
The full-scale invasion of Ukraine by the russian became a bifurcation point for universities located in temporarily occupied territories or war zones, necessitating the search for survival tools in extreme conditions. The crisis management strategy at Kherson State University involved seeking a balance of resources (material, financial, human, communicational, managerial, and innovative) to ensure the proper quality of education. The transformation of business processes accelerated digitalization, and the pursuit of balance in the face of limited resources enabled the implementation of effective anti-crisis measures and the transformation of academic policy aimed at maintaining the quality of the educational process through distance learning technologies, both synchronous and asynchronous interaction formats. This includes a selective component of up to 35% of educational programmes, implementing certificate programmes, and utilizing modern educational resources from global platforms such as Udemy, Coursera, etc. Ensuring sustainable social, professional, and educational communication between dispersed participants in the educational process has become essential to crisis management. The article aims to summarise and systematize the crisis management experience at a displaced university and to model its vital business processes in the context of digital transformation and limited resources, using Kherson State University as an example.